International Journal of Plant Sciences (Chicago, IL : University of Chicago Press, 1992)
Access available from 2010- through JSTOR
Title from cover.
Keywords: Botany -- Periodicals; Botany -- Periodicals; Plantes -- Périodiques.; Plantkunde